2015
DOI: 10.1017/lis.2014.8
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive μXRF analysis of glass and metal objects from sites in the Libyan pre-desert and Fazzan

Abstract: This paper reports on the non-destructive analysis of 42 samples of copper alloy and glass from sites in Libya, using semi-quantitative μXRF, carried out as part of the work of the Trans-Sahara Project funded by the European Research Council. These are among the first chemical analyses to be performed on metals and glasses of any period found in Libya, and the results – though preliminary – raise some interesting possibilities. In particular, we discuss some possible indications with regard to the practice of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The Trans-Sahara project carried out analysis of materials from the Daniels’ excavations to investigate the themes of trade and mobile technologies within the frame of this large ERC-funded project. In particular, Cuénod looked at the compositional signatures of copper alloys in Fazzan, establishing that some of these were certainly of Mediterranean origin and revealing clear evidence of Garamantian reworking of these metals (Duckworth et al 2015; Leitch et al 2017). Similarly, Duckworth's analysis of vessel glass, glass beads and bangles demonstrated that as well as importing material from the Mediterranean, the Garamantes were actively recycling some of this glass and making their own beads (Duckworth et al 2015; 2016a/b).…”
Section: Archive-based Research Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trans-Sahara project carried out analysis of materials from the Daniels’ excavations to investigate the themes of trade and mobile technologies within the frame of this large ERC-funded project. In particular, Cuénod looked at the compositional signatures of copper alloys in Fazzan, establishing that some of these were certainly of Mediterranean origin and revealing clear evidence of Garamantian reworking of these metals (Duckworth et al 2015; Leitch et al 2017). Similarly, Duckworth's analysis of vessel glass, glass beads and bangles demonstrated that as well as importing material from the Mediterranean, the Garamantes were actively recycling some of this glass and making their own beads (Duckworth et al 2015; 2016a/b).…”
Section: Archive-based Research Projectsmentioning
confidence: 99%
“…In particular, Cuénod looked at the compositional signatures of copper alloys in Fazzan, establishing that some of these were certainly of Mediterranean origin and revealing clear evidence of Garamantian reworking of these metals (Duckworth et al 2015; Leitch et al 2017). Similarly, Duckworth's analysis of vessel glass, glass beads and bangles demonstrated that as well as importing material from the Mediterranean, the Garamantes were actively recycling some of this glass and making their own beads (Duckworth et al 2015; 2016a/b). Leitch's detailed work on pottery fabrics has shed light on both handmade and imported Roman productions (Leitch et al 2016; 2017; 2018).…”
Section: Archive-based Research Projectsmentioning
confidence: 99%
“…µXRF is certainly a valuable technique for the characterization of metal alloys, and remains in archaeological contests mainly because it is a non-invasive and non-destructive technique [4][5][6][7][8][9]. In fact, it provides useful information about alloy composition without the necessity of sampling, a step that is often not allowed for metal objects on display in museums [10][11][12][13]. Moreover, the mapping modality can provide knowledge of the whole composition of the surface layer, and can also afford information on the traces of possible surface decorations, even if corrosion patterns must be taken into account [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%